Evaluation of grinding fluids in the grinding of a martensitic valve steel with CBN and alumina abrasives - da Silva, E. J.; Bianchi, E. C.; de Oliveira, JFG; de Aguiar, P. R. (Professional Engineering Publishing Ltd, 2003)
In this paper the performances of different cutting fluids and grinding wheel types were analysed in the grinding of SAE HVN-3 workpieces. The resulting residual stress, wheel wear and roughness were evaluated. The influence of the cutting fluid jet velocity v(j) was also analysed. As a conclusion, the lubrication ability seems to be the governing factor in the cutting fluid performance. The use of CBN wheels can significantly reduce the thermal damage in grinding, leading to compressive residual stresses. The CBN wheel and the cutting oil give an optimum combination for performing this grinding operation.
Keywords: grinding wheel; cutting fluid; residual stress